KONTRIBUSI SUMBER BELAJAR DIGITAL DALAM MENDORONG KETERLIBATAN BELAJAR SISWA SD - Khairunisa Nur Haslinda; Muhammad Muson; Muhammad Yahya Maulida Fahmi; Nada Aulia Nur’aini; Surayanah Surayanah (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT The development of digital technology has transformed the way elementary school students learn, although its utilization in learning has not always been implemented effectively. This article aims to examine the concept of digital learning resources, their forms of integration in learning, and their impact on students’ engagement and independent learning in elementary schools. The research was conducted using a literature review method by examining relevant scientific journals, books, and conference proceedings. The collected data were analyzed using content analysis techniques to identify and synthesize findings from various literature sources. Data validity was maintained through comparison and cross review among sources. The findings indicate that the integration of digital learning resources through blended learning strategies contributes to improving students’ motivation, active participation, and independent learning. These findings emphasize that the use of digital technology can serve as a strategic alternative for creating more interactive and adaptive learning environments. However, its effectiveness is influenced by teachers’ digital competence, the availability of devices, and adequate internet access. Without proper management, the use of digital technology may reduce learning effectiveness. Therefore, strengthening teachers’ digital competence and managing technology based learning should be prioritized to improve the quality of learning in elementary schools. ABSTRAK Perkembangan teknologi digital membawa perubahan pada cara belajar siswa di sekolah dasar, namun pemanfaatannya dalam pembelajaran belum selalu dilakukan secara efektif. Artikel ini bertujuan mengkaji konsep sumber belajar digital, bentuk integrasinya dalam pembelajaran, serta dampaknya terhadap keterlibatan dan kemandirian belajar siswa sekolah dasar. Penelitian dilakukan menggunakan metode tinjauan literatur (literature review) dengan menelaah jurnal ilmiah, buku, dan prosiding yang relevan. Data yang diperoleh dianalisis menggunakan teknik content analysis untuk mengidentifikasi dan mensintesis temuan dari berbagai sumber literatur. Keabsahan data dijaga melalui perbandingan dan kajian ulang antar sumber. Hasil kajian menunjukkan bahwa integrasi sumber belajar digital melalui strategi blended learning berkontribusi dalam meningkatkan motivasi, partisipasi aktif, dan kemandirian belajar siswa. Temuan ini menegaskan bahwa pemanfaatan teknologi digital dapat menjadi alternatif strategis untuk menciptakan pembelajaran yang lebih interaktif dan adaptif. Namun, keberhasilannya tetap dipengaruhi oleh kompetensi digital guru, ketersediaan perangkat, dan akses internet yang memadai. Tanpa pengelolaan yang tepat, penggunaan teknologi digital dapat mengurangi efektivitas pembelajaran. Oleh karena itu, penguatan kompetensi digital guru dan pengelolaan pembelajaran berbasis teknologi perlu diprioritaskan untuk meningkatkan kualitas pembelajaran di sekolah dasar.